Pengaruh Faktor-faktor Kualitas Jasa terhadap Kepuasan Nasabah di Baitul Mal Wat Tamwil (BMT) Tekun Karanggede Boyolali - Tho’in, Muhammad (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2011)
This study aims to determine (1) Is there a significant effect of service quality that consists of tangible, reliability, responsiveness, assurance, and empathy towards customer satisfaction.2 ) Factors of service quality dimensions of the most dominant. The results showed that: (1) There is a significant influence of the quality of service which consists of tangible, reliability, responsiveness, assurance, and empathy towards customer satisfaction. This is evident from the results of regression analysis is to obtain the value Fhitung Ftabel (30,744 2,45) on a significance level of 5%. That is giving evidence on service, reliability personnel in providing service, accuracy in the grasp of officers respond to complaints of customers, providing service guarantees, and giving attention to customer complaints led to customer attention and loyalty to the company, (2) Reliability dimension is the dimension that gives the dominant influence on customer satisfaction. It can be seen from the calculated value of t-hitung reliability dimension (4,004) is higher than other dimensions t-hitung tangibles (3,106), responsiveness (3,779), assurance (2 ,614), and emphaty (3,188). This means that if the reliability in providing services cause customers to feel satisfied.